A descriptive-contrastive analysis of the English passive clauses and the Ilongo-Hiligaynon goal focus clauses - Canieso, Norberto A. 1934- ([Quezon City s.n.], 1971)
This seminar paper is an attempt to analyse the English passive clauses in contrast with the goal focus clauses of Ilongo-Hiligaynon. The socio-cultural setting upon which both languages under study operate is taken as a backdrop of the analysis.
Thesis (M.A.T. English)--University of the Philippines.
Keywords: English language -- Clauses; Hiligaina dialect -- Clauses